1998
DOI: 10.1002/(sici)1096-8628(19980616)78:1<82::aid-ajmg17>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the common critical region in Williams syndrome and clinical correlation of growth, heart defects, ethnicity, and parental origin

Abstract: Williams syndrome (WS) is a neurodevelopmental disorder with a variable phenotype. Molecular genetic studies have indicated that hemizygosity at the elastin locus (ELN) may account for the cardiac abnormalities seen in WS, but that mental retardation and hypercalcemia are likely caused by other genes flanking ELN. In this study, we defined the minimal critical deletion region in 63 patients using 10 microsatellite markers and 5 fluorescence in situ hybridization (FISH) probes on chromosome 7q, flanking ELN. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
2
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 25 publications
7
56
2
4
Order By: Relevance
“…All individuals met the clinical criteria for WS by history and physical findings, but had normal karyotypes. Four of the individuals had been reported previously [Nickerson et al, 1995;Wu et al, 1998] and the other was newly enrolled for the present study (Fig. 1).…”
Section: Ws Patientsmentioning
confidence: 88%
See 3 more Smart Citations
“…All individuals met the clinical criteria for WS by history and physical findings, but had normal karyotypes. Four of the individuals had been reported previously [Nickerson et al, 1995;Wu et al, 1998] and the other was newly enrolled for the present study (Fig. 1).…”
Section: Ws Patientsmentioning
confidence: 88%
“…Our previous studies showed that the majority of WS carry a similar sized deletion spanning an identical number of genes [Wu et al, 1998]. This renders the characterization of genes that contribute to specific features difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WBS patients show mental retardation with a specific cognitive-behavioral profile, supravalvular aortic stenosis, infantile hypercalcemia, a hoarse voice, and distinctive dysmorphic features including an elfin-like face and edematous eyes. The prevalence of WBS in the population is approximately one in 7,500-20,000 (Ewart et al, 1993;Stromme et al, 2002;Wu et al, 1998). Almost all deletions of 7q11.23 in patients with WBS have arisen by de novo mechanisms.…”
Section: Introductionmentioning
confidence: 99%